2007
DOI: 10.1002/dvdy.21126
|View full text |Cite
|
Sign up to set email alerts
|

Validating in utero electroporation for the rapid analysis of gene regulatory elements in the murine telencephalon

Abstract: With the ultimate goal of understanding how genetic modules have evolved in the telencephalon, we set out to modernize the functional analysis of cross-species cis-regulatory elements in mouse. In utero electroporation is rapidly replacing transgenesis as the method of choice for gain-and loss-of-function studies in the murine telencephalon, but the application of this technique to the analysis of transcriptional regulation has yet to be fully explored and exploited. To empirically define the developmental sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
48
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 58 publications
7
48
0
Order By: Relevance
“…We found comparable distributions of targeted cells in control cortices and in cortices electroporated with pCAGGS-Foxp2-3ЈUTR-WT (Fig. 5A,G,I), consistent with previous studies (De Pietri Tonelli et al, 2006;Langevin et al, 2007). By contrast, in cortices electroporated with pCAGGS-Foxp2-⌬-3ЈUTR and pCAGGS-Foxp2-3ЈUTR-MT1+2+3, we found that many of the targeted cells were misplaced in the IZ (Fig.…”
Section: Ectopic Foxp2 Expression Impairs Radial Migration Of Targetesupporting
confidence: 91%
See 1 more Smart Citation
“…We found comparable distributions of targeted cells in control cortices and in cortices electroporated with pCAGGS-Foxp2-3ЈUTR-WT (Fig. 5A,G,I), consistent with previous studies (De Pietri Tonelli et al, 2006;Langevin et al, 2007). By contrast, in cortices electroporated with pCAGGS-Foxp2-⌬-3ЈUTR and pCAGGS-Foxp2-3ЈUTR-MT1+2+3, we found that many of the targeted cells were misplaced in the IZ (Fig.…”
Section: Ectopic Foxp2 Expression Impairs Radial Migration Of Targetesupporting
confidence: 91%
“…3A). Consistent with previous reports (De Pietri Tonelli et al, 2006;Langevin et al, 2007), analysis of fluorescence in electroporated brains 8, 48 or 4 days after electroporation confirmed that expression of mCherry was restricted to the population of targeted neural progenitors in VZ/SVZ (Fig. 3B), or was located in both targeted progenitors and neurons that were generated by them (Fig.…”
Section: Foxp2 3јutr Can Yield Post-transcriptional Repression Of Lucsupporting
confidence: 91%
“…In utero electroporation was performed on pregnant CD-1 mice at E13 according to published protocols (Langevin et al, 2007;Saito and Nakatsuji, 2001). Embryos were collected at 20 hours, 48 hours and 5 days following in utero electroporation, or 2 weeks postnatal.…”
Section: Surgical Proceduresmentioning
confidence: 99%
“…a significant percentage of mt Mcl1-transfected NPCs were already in the CP and (2) GFP and transgene expression from the pCIG2 plasmid are observed by 9 h.p.e. (Langevin et al, 2007). Pregnant dams received an intraperitoneal injection of BrdU at 12 h.p.e.…”
Section: Does Mcl1 Promote Npc Differentiation?mentioning
confidence: 99%
See 1 more Smart Citation